Rock-Eval analysis and organic petrographical characterization of the Upper Jurassic Naokelekan Formation, northern Mesopotamian basin, Kurdistan Region-Iraq - Abdula, Rzger; Kolo, Kamal; Damoulianou, Maria-Elli; Raftopoulou, Victoria; Khanaqa, Polla; Kalaitzidis, Stavros (Bulletin of the Geological Society of Greece, 2020)
The aim of this study is to assess the type, thermal maturity and the petroleum generation potential of the Upper Jurassic Naokelekan Formation, occurring across the Kurdistan Region of Iraq, by applying organic petrographical methods and Rock-Eval analysis. The Rock-Eval data would indicate the presence of kerogen types III, IV and II as the main constituents. However, the qualitative petrographical evaluation revealed that the main organic constituents are solid hydrocarbons, in the form of microgranular migrabitumens, with minor amounts of pyrobitumens. These secondary particles have affected the results of the Rock-Eval analysis and would have led to misinterpretation of organic matter typification based on pyrolysis results only. The combined results of petrography and pyrolysis indicate an active petroleum system within the Upper Jurassic sequence, where hydrocarbons are generated and reservoired within suitable lithologies.